Pedagang Usaha Kecil Menengah (UKM) Berbasis Syariah pada Masyarakat Transimgran di Kota Sorong. - Syahrul; Ariska, Aas Tri; Pujiastuti, Eka Dwi (LPPM IAIN Sorong, 2019)
This paper attempts to unravel the urban economy in Sorong by analyzing the activities of transmigrants who work as traders in small and medium enterprises (UKM). This article finds that the existence of UKM is increasingly, this can be seen along the Km.10, Sorong city. So, it is not surprising to say that UKM are the main pillar of the development and economic growth of the Sorong, especially those carried out by immigrants. The UKM most in demand by immigrants is the culinary business.